Reproductive performance of indigenous goats in traditionally managed flocks in north-east of Zimbabwe - Ndlovu, L.R. (1992)
A study was conducted to define kidding intervals and identify causes for long kidding intervals in communal area flocks. Two flocks were selected in the north-eastern part of Zimbabwe and were monitored over two years. Flock entries and exits were recorded, body-mass changes measured fortnightly and blood samples collected in five consecutive weekly intervals in August-September 1988 and March-April 1989. The average kidding interval for does that kidded in August-December (382 ± 90 days) was longer (P<0.01) than that for does that kidded in March-April (265 ± 48 days). The overall average kidding interval was 370 ± 122 days. Serum progesterone levels also indicated that of the 26 goats that kidded in October-December 1988, 65% were non-pregnant 5-6 months after kidding. It is suggested that nutritional stress could be the cause of these long kidding intervals.